2010
DOI: 10.1175/2009waf2222245.1
|View full text |Cite
|
Sign up to set email alerts
|

An Object-Oriented Multiscale Verification Scheme

Abstract: Object-oriented verification methodology is becoming more and more common in the evaluation of model performance on high-resolution grids. The research herein describes an advanced version of an object-oriented approach that involves a combination of object identification on multiple scales with Procrustes shape analysis techniques. The multiscale object identification technique relies heavily on a novel Fourier transform approach to associate the signals within convection to different spatial scales. Other fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 4 publications
(9 reference statements)
1
36
0
Order By: Relevance
“…One interesting finding in the verification was that the strength parameter was not as useful as expected in discerning between good and poor tracks. It has been suggested that, in addition to a cost function based on the distance from a forecast position, a strength parameter might be useful in matching objects to existing tracks within a tracking algorithm, such as that done by Lack et al (2010). If strength is of limited utility in discerning between good tracks and bad tracks, incorporating strength into a cost function may not significantly improve tracking.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding in the verification was that the strength parameter was not as useful as expected in discerning between good and poor tracks. It has been suggested that, in addition to a cost function based on the distance from a forecast position, a strength parameter might be useful in matching objects to existing tracks within a tracking algorithm, such as that done by Lack et al (2010). If strength is of limited utility in discerning between good tracks and bad tracks, incorporating strength into a cost function may not significantly improve tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Some promising methods are listed here: Contiguous Rain Area (CRA; Ebert and McBride, 2000), Intensity Scale (Casati et al, 2004), Method for Object-based Diagnostic EvaluationÁ (MODE; Davis et al, 2006), FSS (Roberts and Lean, 2008), Structure, Amplitude and Location (SAL; Wernli et al, 2008), and Procrustes Shape Analysis (Lack et al, 2010). Ahijevych et al (2009) carried out idealised and real test cases to gain a basic understanding of behaviour of each method.…”
Section: Brief Review Of Qpf Verification Methodsmentioning
confidence: 99%
“…For example, here the shape of an object is approximated by an ellipse. But it is possible to use more sophisticated methods of shape analysis (Bookstein, 1991;Lack et al, 2010;Micheas et al, 2007;Lakshmanan et al, 2009) to model more complex shapes.…”
Section: Conclusion and Discussionmentioning
confidence: 99%